Service Innovation At Public Service Malls In Improving The Quality Of Public Services In Bandung City - Siti Nurhayati; Rd. Achmad Buchari; Slamet Usman Ismanto (Universitas Sultan Ageng Tirtayasa, 2024)
This research is about service innovation at service malls to improve the quality of public services in the city of Bandung. Public service malls are expected to provide quality, effective, and efficient services. However, there are several problems, namely: there is a gap in the utilization of the number of employees; several counters registered at the Bandung City Public Service Mall are not carried out routinely; and standard operating procedures (SOP) for macro MPP service mechanisms are not yet available. The research method used is qualitative with a descriptive approach, involving observation, in-depth interviews, and documentation studies. The results show the innovation of public service mall services. Cities need effective leadership and good management to coordinate MPP operations and improve service efficiency. The evaluation shows that MPP Bandung City faces challenges such as irregular service times and a lack of comprehensive risk management SOPs. Proposed solutions include increasing human resources, affirming operational time regulations, developing SOPs, and using technology to support service efficiency.